The Complete Works of Gerrard Winstanley. Edited by Thomas N. Corns, Ann Hughes, and David Loewenstein - Rowland, Christopher (The journal of theological studies, 2010)
This long-awaited edition of the complete works of Gerrard Winstanley will be warmly welcomed by historians, students of early modern literature, political theorists, and theologians alike. By any criteria Gerrard Winstanley (1609–76) was a creative theologian, biblical exegete, and social activist. As the editors of the new edition comment, ‘Winstanley compares with the finest writers of that glorious age of English non-fictional prose that extended from the contrasting accomplishments of John Donne and Francis Bacon, through the pyrotechnic power of John Milton, to the fierce sardonic wit of Andrew Marvell and the resonant simplicities of John Bunyan’. A fitting testimony to the power and appeal of this remarkable writer., The crucial word in the description of this book is complete.